The VMC survey - XVI. Spatial variation of the cluster formation activity in the innermost regions of the Large Magellanic Cloud - Piatti, Andres Eduardo (2015)
We present results based on YJKs photometry of star clusters in the Large Magellanic Cloud (LMC), distributed throughout the central part of the galaxy's bar and the 30 Doradus region. We analysed the field-star-decontaminated colour-magnitude diagrams of 313 clusters to estimate their reddening values and ages. The clusters are affected by a mean reddening of E(B - V) ∈ [0.2, 0.3] mag, where the average internal LMC reddening amounts to ~0.1- 0.2 mag. The region covering 30 Doradus includes clusters with reddening values in excess of E(B - V) = 0.4 mag. Our cluster sample spans the age range 7.0 ≤ log (t yr-1) < 9.0, represents an increase of 30 per cent in terms of the number of clusters with robust age estimates and comprises a statistically complete sample in the LMC regions of interest here. The resulting cluster frequencies suggest that the outermost regions of the LMC bar first experienced enhanced cluster formation - log (t yr-1) ∈ [8.5, 9.0] - before the activity proceeded, although in a patchy manner, to the innermost regions, for log (t yr-1) < 7.7. Cluster frequencies in the 30 Doradus region show that the area is dominated by very recent cluster formation. The derived star formation frequencies suggest that the cluster and fieldstar populations do not seem to have fully evolved as fully coupled systems during the last ~100 Myr.